Sistem Pendukung Keputusan Menentukan Aplikasi Chat Terbaik Menggunakan Metode OCRA Dengan Pembobotan ROC - Ardinsah Ardinsah; Mesran Mesran; Agung Triayudi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In this study, a study was conducted to determine the Best Chat Application, the more we enter the digital era, the more applications and communication media or sending messages that appear. So researchers want to do research to determine which chat application is the best that people can use and unfortunately it is suitable for use today, then a system is applied that can help to decide, namely a Decision Support System (DSS) which can simplify the process of selecting the Best Chat Application by implementing 5 criteria i.e. Security, Number of Downloads, Reviews, Features, Storage. So we need a system that can make decisions by using SPK that applies the ROC and Operational Comprtitiveness Rating Analysis(OCRA) methods in getting the weighting value for each criterion and preference value from the best alternative, namely alternative A¬1 with the name Whatsapp Application with a preference value of 128,3123